2013
DOI: 10.1186/2049-9256-1-14
|View full text |Cite
|
Sign up to set email alerts
|

Post-stroke depression and the aging brain

Abstract: Ageing is associated with changes in the function of various organ systems. Changes in the cardiovascular system affect both directly and indirectly the function in a variety of organs, including the brain, with consequent neurological (motor and sensory performance) and cognitive impairments, as well as leading to the development of various psychiatric diseases. Post-stroke depression (PSD) is among the most frequent neuropsychiatric consequences of cerebral ischemia. This review discusses several animal mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 133 publications
1
12
0
1
Order By: Relevance
“…Similar findings with significant rise in the TBARS levels were reported by results of the authors who analysed the level of TBARS after MCAO of various duration (1-2 hr), followed by reperfusion either in hippocampus [51] or in cortical tissue [52,53]. In addition, Cano et al [54] and Cojocaru et al [55] showed also that induction of lipid peroxidation was significantly increased in human ischaemic stroke within the first 24 hr. It is considered that a rise in lipid peroxidation is a valuable early marker of I/R injury developed in a period in which there were still no signs of severe neuronal damage or death [56].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar findings with significant rise in the TBARS levels were reported by results of the authors who analysed the level of TBARS after MCAO of various duration (1-2 hr), followed by reperfusion either in hippocampus [51] or in cortical tissue [52,53]. In addition, Cano et al [54] and Cojocaru et al [55] showed also that induction of lipid peroxidation was significantly increased in human ischaemic stroke within the first 24 hr. It is considered that a rise in lipid peroxidation is a valuable early marker of I/R injury developed in a period in which there were still no signs of severe neuronal damage or death [56].…”
Section: Discussionsupporting
confidence: 84%
“… and Cojocaru et al . showed also that induction of lipid peroxidation was significantly increased in human ischaemic stroke within the first 24 hr. It is considered that a rise in lipid peroxidation is a valuable early marker of I/R injury developed in a period in which there were still no signs of severe neuronal damage or death .…”
Section: Discussionmentioning
confidence: 84%
“…Recovery is slower and incomplete in aged animals 5 even with smaller infarct volumes 4 . Comorbidities such as hypertension, obesity, diabetes, dyslipidemia and increased systemic inflammation increase the probability of poor outcomes in older patient 18 30 31 . Recent reports suggest that both social isolation and feelings of loneliness can increase the risk of illness and death in humans 11 18 .…”
Section: Discussionmentioning
confidence: 99%
“…So far in scientific findings, the etiopathogenesis of the disease has been described as multifactorial. The epidemiological characteristics point out that PSD is a disease of the older population and occurs more frequently in and after the sixth decade of life, more often in the male sex [ 2 ] [ 9 ]. Most commonly mentioned risk factors are: functional disability and a severe stroke, often localised in the left orbitofrontal cortex, disturbing the neurotransmitting circles between the cortex and the basal ganglia [ 3 ] [ 10 ] [ 11 ].…”
Section: Introductionmentioning
confidence: 99%